The Effect of Price, Product Quality, and Service Quality on Shopee Customer Satisfaction in DKI Jakarta - Hermansyah, Hermansyah; Yusuf, Yusuf; Rasyid, Erwin (Fakultas Ekonomi Universitas Garut, 2025)
This study explores the impact of price, product performance, and service quality on the satisfaction of Shopee users in Jakarta. The research context is shaped by three main issues: government plans to restrict imports under IDR 1.5 million, frequent consumer complaints regarding product mismatches, and concerns about Shopee’s service quality not substantially enhancing user satisfaction. A quantitative design was employed, with data collected from 100 respondents in Jakarta through structured questionnaires using a Likert scale. Data analysis, conducted with SPSS version 26, involved descriptive statistics, reliability and validity testing, classical assumption assessment, and regression analysis. The results demonstrate that price significantly affects customer satisfaction (p < 0.05), while product quality does not show a meaningful positive effect (p > 0.05). Furthermore, the combined contribution of product and service quality explains 89% of the variance in customer satisfaction, leaving 11% influenced by other factors beyond the scope of this study.